The Volterra series of distortion analysis - Anilionienė, Julija (Lietuvos matematikos rinkinys, 2011)
The Volterra series method of distortion analysis is presented in the analysis of a common emitter circuit. There are presented the model of the integrated circuit and evaluated their non-linearity’s.According to the provided equivalent diagram and using the method of Volterra series, kernels of the respective linear, square and cube system have been figured out. Changes in an operation mode ofa IT within a frequency range influenced by an input signal have been defined taking into account IT parameters and outer elements.
Keywords: Volterra series; Volterra kernels; IC amplifier non-linearity’s; signal distortions